Optoelectronic characteristics of alpha-SiC:H-based P-I-N thin-film light-emitting diodes with low-resistance and high-reflectance N+-alpha-SiCGe:H layer - Chen, YA; Chiou, CF; Tsay, WC; Laih, LH; Hong, JW; Chang, CY (My University, 1997)
The graded-gap a-SiC:II-based p-i-n thin-film light-emitting diodes (TFLED's) with an additional low-resistance and high-reflectance n(+)-a-SiCGe:H layer mere proposed and fabricated on indium-tin-oxide (ITO)-coated glass substrate in this paper. For a finished TFLED, a brightness of 720 cd/m(2) could be obtained at an injection current density of 600 mA/cm(2), and its EL (electroluminescence) threshold voltage was lowered to 8.6 V. in addition, the effects of reflectance and resistance of a-SiCGe:H film an the performance of TFLED were discussed, The optimum rapid thermal annealing (RTA) conditions for fabrication of TFLED after metallization were also studied and employed to improve the optoelectronic characteristics of TFLED.